2009
DOI: 10.2147/opth.s7141
|View full text |Cite
|
Sign up to set email alerts
|

The effect of combined renal and pancreatic transplantation on diabetic retinopathy

Abstract: This case report describes the effect of simultaneous pancreas kidney transplant (SPK) on the diabetic retinopathy (DR) of two male type 1 diabetic patients. The literature on the effect of SPK on DR is reviewed and the evidence surrounding visual function outcomes is discussed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
4
0
2

Year Published

2011
2011
2020
2020

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 14 publications
(24 reference statements)
2
4
0
2
Order By: Relevance
“…Our study confirms these results and shows that improvement in retinopathy is maintained at the longer follow-up period of 4 years, as already observed after SPK [34,35]. Also, our series of PTA confirms the positive impact on diabetic neuropathy, as previously reported after SPK, PAK, and PTA [36].…”
Section: Discussionsupporting
confidence: 92%
“…Our study confirms these results and shows that improvement in retinopathy is maintained at the longer follow-up period of 4 years, as already observed after SPK [34,35]. Also, our series of PTA confirms the positive impact on diabetic neuropathy, as previously reported after SPK, PAK, and PTA [36].…”
Section: Discussionsupporting
confidence: 92%
“…Several studies conducted in our laboratory have previously shown that PT is not only able to restore the endocrine balance in ALX-induced diabetic rats but can also prevent or stabilize the progression of diabetic lesions in the kidneys, eyes, nerves and lungs of these animals [45][46][47][48]. These findings have been confirmed by others in humans [4][5][6][7]. However, studies on the effects of PT on testicular lesions are rare, particularly those involving long-term follow-up for up to 50 weeks after transplantation or until 62 weeks of age.…”
Section: Discussionsupporting
confidence: 69%
“…Successful pancreas transplantation (PT) is currently seen as the only treatment that can modify the expected natural history of diabetic complications in insulin-dependent DM, as is able to delay the progression, stabilize, and even reverse many complications of the disease in the kidneys, vessels, eyes, and nerves of patients [4][5][6][7].…”
Section: Introductionmentioning
confidence: 99%
“…Thus, retinal complications associated with these conditions may be expected in this group of patients. Previously existing diabetic retinopathy may worsen, remain stable or improve, 4 - 8 and post-transplantation blood glucose control does not halt its progression, especially in patients not receiving adequate specific treatment in the preoperative period. 4 …”
Section: Discussionmentioning
confidence: 99%